PVT DATA ESTIMATION FOR RESERVOIR FLUIDS OF FASHA AND GIR FORMATIONS IN GHANI OILFIED, LIBYA - Seham N. Tawfic; Ibrahim M. Abou El Leil; Somaya A. Altayeb (Surman Journal of Science and Technology, 2024)
PVT properties are very important in reservoir and production engineering analyses such as material balance calculations, well testing, reserve estimation, inflow performance, production operations and design of surface facilities. It is used to distinguish the properties of reservoir fluids, which is significant in various reservoir studies. The current paper is about a case study of the Ghani oilfield. This study was conducted to highlight PVT data analysis for Ghani oil field that carried out on two wells namely and Well XX 11-11 including two rock formations are Facha and Gir Formations respectively. The primary objective of this study is to present the most commonly used PVT correlations and properties for saturation pressure (psat), solution gas/oil ratio (Rs), oil density ( ), deviation factor (z) and the gas formation volume factor (Bg) at saturation pressure. A subsurface sample was collected from the subjected wells for use in a reservoir fluid study. The results that obtained from different tests revealed that the hydrocarbon composition analysis of the studied fluid for the investigated Well XX-1-11 of Facha Formation shows heptanes plus 59.91 mole percent, with specific density 0.8463 and API 35.5; while in Well XX 11-11 of Gir Formation is 54.76 mole percent with specific density, 0.8476 and API 35.3. The saturated pressures are 283 and 351 psig with viscosity 1.02 and 1.37 centipoise at 130 and 122ºF respectively. The results of reservoir fluid data of separation tests showing a variation in values for the investigated parameters e. g., gas/oil ratio, stock tank gravity (ºAPI), formation volume factor, separator volume factor and specific gravity of flashed gas at different ranges of pressure and separator temperature 75ºF for both the two wells. The hydrocarbon analysis of separator gas samples were examined at different conditions e. g. 80 @ 75ºF, 40 @ 75ºF and 0 psig @ 75ºF. The components of studied hydrocarbons are varied with changing separator conditions.